Characterization of fungal community associated with house dust - Amaro, Raquel do Nascimento (2016)
With the increasing urbanization, the world population spends more and more time indoors, where exposure to contaminants inside buildings can be high. This scenario leads to a degradation of Indoor Air Quality (IAQ), which, in extreme cases, can lead to Sick Building Syndrome (SBS). Fungi can be found in all types of environments and the fungal community found inside buildings plays an essential role in the health of individuals that use these locations. Dust in particular, acts as a reservoir of all contaminants inside buildings, including fungi and can be used to characterize the indoor environment. The coexistence of individuals with the fungi in the interior of a building is not always beneficial to health. There are strong associations between the patients with respiratory allergies and sensitization to molds where the latter play an important role in the development, persistence and severity of the former. For this type of immunologically susceptible individuals, exposure to fungal contamination can trigger respiratory symptoms such as asthma. Thus, this work aims in a first stage to characterize the fungal community in house dust samples from houses built along different decades using different dust sampling procedures and in a second stage to characterize the fungal community in dust from the houses of asthmatic patients and respective controls in order to unravel possible associations. This work was divided into two key points: i) to identify the fungal community in house dust and its abundance ii) to associate the fungal genera found with the severity of asthma. The most abundant fungal genera found were Aspergillus, Penicillium, Cladosporium, Alternaria and yeast. As for the association to asthma exacerbations, no association was found. However, given the preliminary nature of point ii), a larger number of samples will be necessary in order to draw any robust conclusions